Venezuela’s Energy Transition: A Synergistic Approach to Blue Hydrogen, AI, and LNG Development. - Cabrera, Kelvin (International Journal of Educational Practices and Engineering(IJEPE), 2025)
Background: Venezuela faces critical challenges in its transition to a sustainable energy matrix, due to its historical dependence on hydrocarbons, economic instability and the obsolescence of its energy infrastructure. Despite having the largest natural gas reserves in Latin America (200.3 trillion cubic feet), the country has yet to take advantage of emerging opportunities such as the production of blue hydrogen, a key energy vector for decarbonizing carbon-intensive economies. Objective: To evaluate the potential of blue hydrogen as a strategic solution for Venezuela's energy transition, considering the use of advanced technologies such as artificial intelligence (AI) and liquefied natural gas (LNG). Method: An exploratory and descriptive approach was adopted, based on a comprehensive review of scientific literature, International Energy Agency (IEA) technical reports, PDVSA publications and international case studies. The analysis included the identification of recurring themes and the assessment of opportunities and threats. Results: The Perla, Quiriquire Gas and Petrocarabobo projects show potential to be integrated into decarbonization strategies through advanced technologies such as AI and carbon capture and storage (CCS). In addition, AI optimizes critical processes such as geological analysis, demand forecasting and safety monitoring, reducing operating costs by up to 20%. However, significant structural barriers remain, such as lack of foreign investment, political and economic instability, and the need to modernize energy infrastructure. Conclusions: To successfully integrate blue hydrogen, AI and LNG, significant investments, regulatory reforms, specialized training and international collaboration are required. These efforts are essential to position Venezuela as a regional leader in clean energy production and contribute to sustainable development in Latin America.